2020
DOI: 10.1002/eqe.3371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kinematic interaction on seismic response of offshore wind turbines on monopiles

Abstract: Interest in renewable energy over the past decade has motivated a remarkable research on offshore wind energy. Due to the environmental loading conditions in the early developments of offshore wind farms, the focus of the research and engineering has been on aerodynamic and hydrodynamic subjects. However, earthquake has turned out to be a major design concern in seismic areas such as East Asia, Southern Europe, and United States. The topics include, among others, nonlinear response of foundations, soil liquefa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…44 Given the complexity of the grouted connection model and the associated high computational cost, the selection of a limited number of relevant earthquake motions was essential. As such, two earthquake records were selected for this study, enabling direct comparison with published work on offshore turbines under seismic loads 17,18,45 : (i) Kobe, Japan, Nishi-Akashi, January 17, 1995, and (ii) Chi-Chi Taiwan-03, CHY082, September 20, 1999. These were also selected because of their significantly contrasting characteristics, enabling further insight into the dynamic behaviour of the structure under varying seismic loads:…”
Section: Seismic Loadsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Given the complexity of the grouted connection model and the associated high computational cost, the selection of a limited number of relevant earthquake motions was essential. As such, two earthquake records were selected for this study, enabling direct comparison with published work on offshore turbines under seismic loads 17,18,45 : (i) Kobe, Japan, Nishi-Akashi, January 17, 1995, and (ii) Chi-Chi Taiwan-03, CHY082, September 20, 1999. These were also selected because of their significantly contrasting characteristics, enabling further insight into the dynamic behaviour of the structure under varying seismic loads:…”
Section: Seismic Loadsmentioning
confidence: 99%
“…Research of the structural behaviour of offshore wind turbines under dynamic loads is increasing. De Risi et al 14 Vacareanu et al 15 and Kaynia 16,17 showed high sensitivity of OWT structures to historical seismic events, accounting for the combination of seismic and environmental (wind/wave) loading. Sensitivity to the operational conditions (e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zhao et al, (2020) used a response spectrum method to evaluate the OWT's pile-water and pile-soil interactions, also pointed out that pile-water interaction significantly affects the structural displacement. In recent work, Kaynia, (2020) presented the effect of kinematic interaction through the numerical of monopole OWT. Higher kinetic interaction is noted for the stiff soil and medium-to-high frequency content.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The filtering of seismic ground motion due to soil-pile interaction has been established using several closed form analytical solutions, 11,[16][17][18][19][20] boundary element formulations 21,22 as well as numerical models. [23][24][25][26][27][28][29][30] Studies by Gazetas and Dobry 19 and Kaynia and Kausel 20 showed that the filtering of the free-field motion was stronger in inhomogeneous soil profiles when compared to homogeneous profiles. Simplified expressions for the kinematic interaction factor for single piles have also been proposed in past studies.…”
Section: Introductionmentioning
confidence: 99%